ORAL HYGIENE PROTOCOLS FOR PATIENTS IN INTENSIVE CARE UNIT: PROTOCOLOS DE HIGIENE BUCAL PARA PACIENTES EM UNIDADE DE TERAPIA INTENSIVA - da Silva Reginato, Bianca; Gomes Dallepiane, Felipe; Jorge Corralo, Daniela (Revista de Ciências da Saúde Nova Esperança, 2023)
This literature review aimed I’m verify which are the most effective hygiene protocols and oral antiseptics in reducing or preventing ventilator-associated pneumonia (VAP). A search for related articles was carried out in the pubmed and science databases , selecting by title , abstract and full text , excluding those whose theme was not in accordance with the research objective . it was found that although there are several ways I’m control biofilm , there is still no established protocol for oral hygiene of patients study mechanical ventilation , having identified different methods including the use of various antiseptic products , such as chlorhexidine 0.12, 0.2 and 2%, associated or not with a mechanical method of biofilm removal . In some protocols , the use of more than one substance is suggested , such as hydrogen peroxide, associated with cetylpyridinium chloride or chlorhexidine . However , more comprehensive protocols , involving measures other than mechanical and pharmacological methods , proved I’m be more efficient in preventing and reducing VAP. antiseptics are very important for reducing the rate of this infection , although several substances have been tested , chlorhexidine gluconate is the most indicate by the authors .